Design and Development of Engklek Carpet Learning Media for Early Childhood Motor Stimulation - Riya Wahyuni; Hamidah Apriani; Roni Kurniawan (fakultas Desain Komunikasi Visual, 2026)
Early childhood education requires varied and enjoyable media to stimulate optimal child development, but the availability of media that integrate motor, cognitive, language, and social-emotional aspects is still limited. This study aims to develop interactive learning media in the form of an engklek carpet to stimulate fine and gross motor skills in children aged 3-6 years while introducing traditional games. The method used is Research and Development with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, observations, literature studies, and documentation at PG & TK Islam Nurul Hasanah East Jakarta. The results showed that the engklek carpet media was successfully developed by integrating four types of games that adapted the traditional games of engklek tapak gunung/tapak bulan and engklek sliding. The design uses bright colors, representative illustrations, and a box size of 30 x 30 cm according to the characteristics of early childhood. A trial on 20 Kindergarten B students showed that students participated in activities enthusiastically, orderly, and were able to achieve development indicators in the aspects of art, language, cognitive, physical-motor, and social-emotional. The conclusion of this study is that the hopscotch carpet media is suitable for use as an effective PAUD learning medium to increase children's interest in learning and contribute to the preservation of local culture.